Murasaki Shikibu the Tale of Genji - Bowring, Richard 1947- (Cambridge University Press, 2004)
Murasaki Shikibu's The Tale of Genji, written in Japan in the early eleventh century, is acknowledged to be one of Japan's greatest literary achievements, and sometimes thought of as the world's first novel. It is also one of the earliest major works to be written by a woman. This introduction to the Genji sketches the cultural background, offers detailed analysis of the text, discusses matters of language and style and ends by tracing the history of its reception through nine centuries of cultural change. This book will be useful for survey courses in Japanese and World Literature. Because The Tale of Genji is so long, it is often not possible for students to read it in its entirety and this book will therefore be used not only as an introduction, but also as a guide through the difficult and convoluted plot
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Murasaki Shikibu / 978?- / Genji monogatari; Murasaki Shikibu -- 978-1016; Murasaki Shikibu -- 978-1016 -- Genji monogatari